Health Education About Perineum Massage for Pregnant Women in the Work Area of the Kamoning Sampang Community Health Center - Mudlikah, Siti; Safriana, Rizka Esty; Ningsih, Dwi Purwati (Universitas Islam Lamongan, 2020)
Perineal bleeding due to tears is one of the causes of maternal death. efforts to prevent perenium tears by performing perineum massage techniques in third trimester pregnant women at 34-35 weeks' gestation. The purpose of this study was to determine the effect of health education on perineal massage on the knowledge of pregnant women in the working area of the kamoning puskesmas in Sampan District, Sampang Regency. The research method used one group pre-post test design, questionnaire instruments, population of trimester III pregnant women amounted to 120 people, total sampling samples, analysis of frequency distribution data, T-test statistical test. The results of the study were obtained from 120 third trimester pregnant women before being given knowledge good about health education (5.8%), enough (36.7%) and less (57.5%), while the knowledge of pregnant women in the third trimester after being given knowledge about good health education (78.3%), enough (20 , 9%) and less (8%). The T test found that p (value) = 0.005 and Î± = 0.05, it means p (value) <Î± so that there is an influence of health education about perineal massage on the knowledge of trimester pregnant women. Conclusion: there is an effect of health education about perineal massage on the knowledge of third trimester pregnant women in the working area of the Sampang Community Health Center.Â Keywords: Health, Education, Massage, Perineum